PERTANGGUNGJAWABAN PIDANA BAGI SAKSI YANG MEMBERIKAN KESAKSIAN PALSU DI BAWAH SUMPAH DALAM PERSIDANGAN - Nauli Marsusila Lubis; Ridwan Arifin (MORALITY: Jurnal Ilmu Hukum, 2019)
The witness became an important element in the trial, especially in matters of criminal law. As the main evidence, of course a witness has a very large contribution in efforts to uphold law and justice. In resolving a criminal case, the position of the witness is an important matter in proving a criminal case. The Criminal Justice System clearly regulates how the witness should provide information about his testimony in the trial. The rights and obligations of witnesses are also regulated, including rights and witness protection. However, it cannot be denied that the information provided by witnesses is not necessarily the truth. Some of them, gave testimony by adding elements of lies or even conveying false statements. Ironically, the testimony or statement submitted was an oath statement, which meant the witness dared to lie even though he had taken an oath. False information under oath is a statement that is partially or completely incorrect, so that in the implementation of article 242 of the Criminal Code (KUHP), punishment is arranged for the person so that the offender who has deliberately provided the false information, can be sentenced. This paper analyzes how the criminal liability of witnesses gave false information in the trial.